The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1128/aem.00467-21
|View full text |Cite
|
Sign up to set email alerts
|

Legionella pneumophila CRISPR-Cas Suggests Recurrent Encounters with One or More Phages in the Family Microviridae

Abstract: Legionella pneumophila is a ubiquitous freshwater pathogen and the causative agent of Legionnaires’ disease. L. pneumophila growth within protists provides a refuge from desiccation, disinfection, and other remediation strategies. One outstanding question has been whether this protection extends to phages. L. pneumophila isolates are remarkably devoid of prophages and to date no Legionella phages have been identified. Neverthel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…Other invasive elements known to integrate at the dif site of their host (IMEXs) do not encode their own recombinase and instead utilize the host Xer for integration/excision (Das et al, 2013;. Similarly, LME-1 does not appear to encode its own recombinase or integrase (Deecker et al, 2021). Our intermolecular recombination assay indicates that XerL can facilitate integration of circular DNA containing the LME-1 22-bp att site (Fig.…”
Section: Deletion Of Dif or Lpg1867 Induces Filamentation And Inhibits Growthmentioning
confidence: 83%
See 1 more Smart Citation
“…Other invasive elements known to integrate at the dif site of their host (IMEXs) do not encode their own recombinase and instead utilize the host Xer for integration/excision (Das et al, 2013;. Similarly, LME-1 does not appear to encode its own recombinase or integrase (Deecker et al, 2021). Our intermolecular recombination assay indicates that XerL can facilitate integration of circular DNA containing the LME-1 22-bp att site (Fig.…”
Section: Deletion Of Dif or Lpg1867 Induces Filamentation And Inhibits Growthmentioning
confidence: 83%
“…Several strains of Legionella pneumophila harbor a phage-like integrative mobile genetic element, named Legionella mobile element-1 (LME-1) (Deecker et al, 2021;Lüneberg et al, 2001;Rao et al, 2016). We previously found that integration into the genome requires a 22-bp attachment site (att) in LME-1 that is identical to a sequence on the L. pneumophila genome (Rao et al, 2016).…”
mentioning
confidence: 99%
“…Based on CRISPR-spacer sequences, it is possible to infer that within the human microbiome, the most commonly infected bacterial genera are Bacteroides, Prevotella, Faecalibacterium, and Phasolarctobacterium (11,90,110). Furthermore, microviral spacers are also present in genera containing pathogens such as Acinetobacter, Burkholderia, Clostridium, Helicobacter, Legionella, and Treponema (11,111). Notably, single-cell viral-tagging has confirmed the CRISPR-based predictions of Gram-positive Actinomycetota (specifically Collinsella) as microviral hosts in the human gut (112).…”
Section: Identifying Hosts and Isolating Microvirusesmentioning
confidence: 99%
“…Several strains of Legionella pneumophila harbor a phage-like integrative mobile genetic element named Legionella mobile element-1 (LME-1) ( 30 33 ). We previously found that integration into the genome requires a 22-bp attachment site ( att ) in LME-1 that is identical to a sequence on the L. pneumophila genome ( 33 ).…”
Section: Introductionmentioning
confidence: 99%